Factors contributing to the transverse shear stiffness of bolted cold-formed steel storage rack upright frames with channel bracing members. (March 2019) - Talebian, Nima; Gilbert, Benoit P.; Baldassino, Nadia; Karampour, Hassan
Abstract: Accurately determining the transverse shear stiffness of steel storage rack upright frames is essential in calculating the elastic buckling load, performing earthquake design and serviceability checks. International racking design specifications recommend different approaches to evaluate this stiffness. The Rack Manufacturers Institute (RMI) specification conservatively uses an analytical solution based on Timoshenko and Gere's theory while the European (EN15512) and Australian (AS4084) specifications recommend experimental testing to be conducted. Previous studies have shown that Finite Element Analyses (FEA), solely using beam elements, fail to reproduce experimental test results and may overestimate the transverse shear stiffness by a factor up to 25. This discrepancy is likely attributed to the local deformations occurring at the bolted joints. In this paper, a model to capture the transverse shear stiffness of upright frames is developed using shell elements and advanced FEA. Its accuracy is verified against published experimental test results performed on three commercially used upright frame configurations with lip-to-lip bracing pattern. The model accurately reproduces the experimental stiffness, with differences ranging from 2% to 17%. Based on the FE model, the factors contributing to the transverse shear deformation of the frames are quantified and discussed for both lip-to-lip and back-to-back bracing patterns. For lip-to-lip upright frames, results show that the local deformations at the end of bracing members contributes the most to the shear deformation of the frames. For back-to-back upright frames, bolt bending and axial deformation of braces contribute the most to the shear deformation of the frames. Results from this paper would assist the racking industry in improving their products by focusing on the factors influencing the most the behaviour of the frames. Highlights: Finite Element (FE) model accurately predicts the transverse shear stiffness of storage rack upright frames with channel bracing members. Contribution of various factors influencing the shear stiffness of the rack upright frames with lip-to-lip and back-to-back channel bracing members. Contribution of various factors influencing the shear stiffness of the rack upright frames according to Australian standards AS4084 and European standard EN15512. Possibility to improve rack design by targeting the factors influencing the most the shear stiffness of the frames.